2013
DOI: 10.1098/rsif.2012.0760
|View full text |Cite
|
Sign up to set email alerts
|

An automated approach for three-dimensional quantification of fibrillar structures in optically cleared soft biological tissues

Abstract: We present a novel approach allowing for a simple, fast and automated morphological analysis of three-dimensional image stacks (z-stacks) featuring fibrillar structures from optically cleared soft biological tissues. Five nonatherosclerotic tissue samples from human abdominal aortas were used to outline the multi-purpose methodology, applicable to various tissue types. It yields a three-dimensional orientational distribution of relative amplitudes, representing the original collagen fibre morphology, identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 51 publications
6
71
0
Order By: Relevance
“…Specifically, in human arterial walls the collagen fibers are not perfectly aligned but are dispersed around a mean direction. Such a fiber dispersion has been observed in, for example, human arterial walls [1][2][3][4][5], the myocardium [6,7], corneas [8,9] and articular cartilage [10]. In particular, recent extensive experimental results [4] have shown that the collagen fiber dispersion in each of the layers of (healthy) human thoracic and abdominal aortas and iliac arteries is non-symmetric, in contrast to the rotationally symmetric fiber dispersion assumed in previous studies; see, for example, [11].…”
Section: Introductionmentioning
confidence: 79%
“…Specifically, in human arterial walls the collagen fibers are not perfectly aligned but are dispersed around a mean direction. Such a fiber dispersion has been observed in, for example, human arterial walls [1][2][3][4][5], the myocardium [6,7], corneas [8,9] and articular cartilage [10]. In particular, recent extensive experimental results [4] have shown that the collagen fiber dispersion in each of the layers of (healthy) human thoracic and abdominal aortas and iliac arteries is non-symmetric, in contrast to the rotationally symmetric fiber dispersion assumed in previous studies; see, for example, [11].…”
Section: Introductionmentioning
confidence: 79%
“…To inform the modelling process, second-harmonic generation, for example, in combination with optical clearing [49] is a powerful technique for obtaining collagen fibre dispersion data from various types of tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In many of these tissues the collagen fibers are distributed around a mean direction in the reference configuration in the ground substance within which the fibers are embedded [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%